Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Emosi Anak Tk Di Desa Mranggen, Kecamatan Polokarto, Kabupaten Sukoharjo Tahun 2015/2016 - Alviyani, Erna (2016)
Children's education should be carried out through three environments, namely family, schools, and organizations. The family is the center of education first and foremost. Since the onset of human civilization until now, the family is always a big influence on the development of a human child. This study aims to determine whether there is a relationship of authoritarian parenting parents on the emotional development of children in the village kindergarten Mranggen, District Polokarto, Sukoharjo Year 2015/2016. This type of research is descriptive quantitative research. Large overall sample taken 73 children with Proportional Random Sampling. The technique of collecting data using questionnaires. Hypothesis testing using product moment correlation analysis. Based on the results of data analysis researchers in testing the hypothesis that it can be seen that the Pearson correlation r value of -0,374 with a significance of 0.001 <0.01 (p = 0.001; p <0.01). It can be concluded that there is a relationship between authoritarian parenting parents on the emotional development of children kindergarten in the village of the District Mranggen Polokarto Sukoharjo Year 2015/2016.